Analgesia Multimodal Pascaoperatif pada Pasien Pediatrik - Widyastuti, Yunita; Sari, Djayanti; Rizki, Gilar (Jurnal Komplikasi Anestesi, 2019)
Acute pain can be found in patient undergoing surgery. Postoperative pain scale is variable from mild to moderate-severe. There are difficulties in assessing pain scale in pediatric, not like adult, pediatric patient can’t say what they feel. Management of postoperative pain, especially in moderate-severe scale needs a multimodal approach to overcome it. The aim of multimodal strategy is to optimize analgetic effect and reduce the adverse effect of the drugs.